A cross-sectional study on the impact of mobile medical units on hypertension awareness and management in rural Himachal Pradesh and Uttarakhand - Mahanta, Banoj Kumar; Sameni, Narayan Rao; Sinha, Sudeep; Sharma, Retisha; Pandey, Surabhi; Jha, Sagar Kumar (International Journal Of Community Medicine And Public Health, 2024)
Background: In India, the shift from communicable to non-communicable diseases such as hypertension is significant. Mobile medical units (MMUs) are among the new initiatives to improve hypertension treatment coverage in rural areas across many countries. The Hans Foundation has implemented Mobile Medical Unit intervention for over a year in the rural areas of Himachal Pradesh and Uttarakhand. This cross-sectional study aimed to investigate the factors affecting hypertension and to evaluate awareness, attitudes, and practices among rural communities, highlighting the effectiveness of MMUs. Methods: In total, 418 randomly selected participants were recruited for this study. The respondents were adults (aged 18+ years) diagnosed with hypertension (systolic BP≥130 and/or diastolic BP≥90), on medication, and enrolled for over three months in Himachal Pradesh and Uttarakhand. Structured/semi-structured questionnaires were used in beneficiary interviews, key informant interviews (KIIs), and focus group discussions (FGDs) to examine the demographic, socioeconomic, and lifestyle factors influencing hypertension awareness and MMU effectiveness in the intervention areas. Results: The study findings revealed a high awareness of hypertension risk factors, with stress being the most recognized (95%) and family history (46%). 54% of the study respondents lacked formal education, and respondents included homemakers (25%) and farmers (17%). Females demonstrated significantly higher awareness of alcohol consumption as a risk factor (64%, p<0.033) and unanimously believed in regular BP monitoring (p<0.004) for hypertension management compared to males. Conclusions: The study emphasized the substantial impact of MMU on health outcomes and accessibility. Participants expressed high satisfaction with MMU services, highlighting their perceived effectiveness of healthcare delivery.